2017
DOI: 10.1016/j.carbon.2016.12.015
|View full text |Cite|
|
Sign up to set email alerts
|

Creating nanoporous graphene with swift heavy ions

Abstract: We examine swift heavy ion-induced defect production in suspended single layer graphene using Raman spectroscopy and a two temperature molecular dynamics model that couples the ionic and electronic subsystems. We show that an increase in the electronic stopping power of the ion results in an increase in the size of the pore-type defects, with a defect formation threshold at 1.22-1.48 keV/layer. We also report calculations of the specific electronic heat capacity of graphene with different chemical potentials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 74 publications
(89 reference statements)
1
47
0
Order By: Relevance
“…This can be achieved by either highly charged or by very fast (swift) heavy ions. For both it has been shown that they can be used for defect engineering of 2D materials such as carbon nano-membranes, 26,27 graphene, [28][29][30][31][32][33] hexagonal boron nitride, 34 and MoS 2 . [35][36][37] Swift heavy ions (SHI) excite target atoms along their trajectory and the corresponding energy deposited per track length into the target material is usually given in terms of electronic stopping power S e = dE/dx.…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by either highly charged or by very fast (swift) heavy ions. For both it has been shown that they can be used for defect engineering of 2D materials such as carbon nano-membranes, 26,27 graphene, [28][29][30][31][32][33] hexagonal boron nitride, 34 and MoS 2 . [35][36][37] Swift heavy ions (SHI) excite target atoms along their trajectory and the corresponding energy deposited per track length into the target material is usually given in terms of electronic stopping power S e = dE/dx.…”
Section: Introductionmentioning
confidence: 99%
“…To introduce defects deliberately and reliably, a variety of processes can be used: direct host atom displacement by electron knock-on in a transmission electron microscope 12 , wet or dry chemical etching 13,14 , as well as focused and broad ion beam irradiation 15 . The latter approach is especially efficient in introducing specific structural defects and substitutional defects with foreign atoms [16][17][18][19] . The efficiency for structural defect formation (defect per ion) increases both with ion mass and decreasing kinetic energy 20,21 , because the ion scattering cross section increases.…”
mentioning
confidence: 99%
“…MD simulations on NP elongation in silica were carried out using the classical MD [24] code PARCAS [25][26][27][28][29], previously widely used to study radiation effects including swift heavy ions [26,[30][31][32]. To initiate the ion track, we followed the practice of instantaneous energy deposition according to a profile obtained from the two-temperature iTS model [33].…”
Section: B Simulationsmentioning
confidence: 99%